KAJIAN PROFIL GIZI BURUK DI KLINIK GIZI PUSAT PENELITIAN DAN PENGEMBANGAN GIZI DAN MAKANAN, BOGOR - ., Sihadi (PERSATUAN AHLI GIZI INDONESIA, 2009)
SEVERE MALNUTRITION PROFILE IN BOGOR CLINICAL NUTRITIONBogor Clinical Nutrition is handling for recovering of children severe malnutrition especially foroutpatient. The handling is done for six months with 12 – 18 times of invitation. The interventionswere done by giving the vitamin A highly doses given at the firs invitation, the curing of infection,nutritional and health education, and given the milk skim for every invitation. The results showed thatafter six month treatment the weight/age the change to become moderate malnutrition 63,9%, andwell nutrition 3,0%. If using the weigh/height index from severe wasting change to be wasting is62,4% - 81,6%.Keywords: marasmus, kwashiorkor, marasmic-kwashiorkor, outpatient